QlikView your business : an expert guide to business discovery with QlikView and Qlik Sense - Troyansky, Oleg; Gibson, Tammy; Leichtweis, Charlie; Ohio Library and Information Network (Indianapolis, IN : Wiley, 2015)
This book shows you how to build dynamic, best-of-breed data visualizations using the QlikView toolset. This full-color, step-by-step guide walks you through the basics of using the tools, then dives deep to provide expert advice on complex implementation techniques and solutions. Coverage includes both QlikView and Qlik Sense, with a focus on the process of developing analytic applications, with scripting and visualization techniques for analyzing sales, profitability, and inventory. You will learn how to analyze your data, determine the appropriate solution, define the data model, and develop the load script and user interface for a complete analytic solution implemented in QlikView, Qlik Sense, or both. --
Getting Started. The Needs and Challenges of Business Intelligence and Analytics -- Why Use Qlik for Data Discovery and Analytics? -- Learning the Core Techniques: Sales Analysis. Defining a Business Scenario for Sales Analysis -- Visualizing Sales Analysis in QlikView -- Data Modeling for Sales Analysis -- Developing a Data Load Script for Sales Analysis -- Expanding Your Skill Set: Profitability Analysis. Defining a Business Scenario for Profitability Analysis -- Visualizing Profitability Analysis in QlikView -- Data Modeling for Profitability Analysis -- Developing a Data Load Script for Profitability Analysis -- Defining a Business Scenario for Inventory Analysis -- Mastering Advanced Techniques: Inventory Analysis. Visualizing Inventory Analysis in QlikView -- Data Modeling for Inventory Analysis -- Developing a Data Load Script for Inventory Analysis -- Qlik Sense. Loading Data in Qlik Sense -- Developing Visualizations in Qlik Sense -- What's Next?
Includes index
Keywords: Business intelligence -- Computer programs; Management information systems; Electronic books